Submarine Groundwater Discharge From Non-Tidal Coastal Peatlands Along the Baltic Sea - Racasa, Erwin Don; Lennartz, Bernd; Toro, Miriam; Janssen, Manon (Frontiers in Earth Science, 2021)
Submarine groundwater discharge (SGD) is an important pathway for water and materials within the land-ocean transition zone that can impact coastal environments and marine life. Although research from sandy shorelines has rapidly advanced in recent years, there is very little understanding of coastal areas characterized by a low hydraulic conductivity, such as carbon-rich coastal peatlands. The objective of this study was to determine the magnitude and location of terrestrial SGD to be expected from a non-tidal low-lying coastal peatland located along the Baltic Sea and to understand the controlling factors using numerical modeling. We employed the HYDRUS-2D modeling package to simulate water movement under steady-state conditions in a transect that extends from the dune dike-separated rewetted fen to the shallow sea. Soil physical properties, hydraulic gradients, geological stratifications, and topography were varied to depict the range of properties encountered in coastal peatlands. Our results show that terrestrial SGD occurs at the study site at a flux of 0.080 m²/d, with seepage rates of 1.05 cm/d (upper discharge region) and 0.16 cm/d (lower discharge region above submerged peat layer). These calculated seepage rates compare to observations from other wetland environments and SGD sites in the Baltic Sea. The groundwater originates mainly from the dune dike – recharged by precipitation and infiltration from ponded peatland surface water – and to a lesser extent from the sand aquifer. The scenario simulations yielded a range of potential SGD fluxes of 0.008 to 0.293 m²/d. They revealed that the location of terrestrial SGD is determined by the barrier function of the peat layer extending under the sea. However, it has little impact on volume flux as most SGD occurs near the shoreline. Magnitude of SGD is mainly driven by hydraulic gradient and the hydraulic conductivity of peat and beach/ dune sands. Anisotropy in the horizontal direction, aquifer and peat thickness, and peatland elevation have little impacts on SGD. We conclude that SGD is most probable from coastal peatlands with high water levels, large Ks and/or a dune dike or belt, which could be an essential source for carbon and other materials via the SGD pathway.